Halpern's iteration for Bregman strongly nonexpansive mappings in reflexive Banach spaces - Suantai S. (2014)
We investigate strong convergence for Bregman strongly nonexpansive mappings by Halpern's iteration in the framework of reflexive Banach spaces. Using the obtained result, convergence for a family of Bregman strongly nonexpansive mappings is also discussed. As applications, we apply our main result to problems of finding zeros of maximal monotone operators and equilibrium problems in reflexive Banach spaces. © 2011 Elsevier Ltd. All rights reserved.